Ogień, woda, ziemia, powietrze: metafory języka w ekolingwistyce = Fire, water, earth, air: language metaphors in ecolinguistics - Steciąg, Magdalena (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of the article is to present the metaphorical basis of thinking about language in ecolinguistics. The "elements of ecolinguistics" are understood on the one hand as a circle of its interests, and on the other - as a source of metaphorical references in ideas about language, in which the four elements of nature return: fire, water, earth and air.
Keywords: ekolingwistyka; metafory języka; językoznawstwo stosowane; ecolinguistics; language metaphors; applied linguistics